Mengembangkan Kecerdasan Interpersonal Anak dengan Bermain Permainan Tradisional - Syiddatul Budury; Khamida Khamida; Nailul Huda (Wisanggeni : Jurnal Pengabdian Masyarakat, 2022)
Indonesian traditional games are now increasingly being abandoned. Children prefer to play online games. The purpose of this community service activity is to develop children's interpersonal intelligence by playing traditional games and introducing traditional games to children. This activity was attended by 12 children aged between 7-12 years in Ar Rasyid Alquran learning center. The activity was carried out for 4 meetings, each meeting played a different game; Bantengan, Gobaksodor, Dakon and Engkle. Children's interpersonal intelligence was measured through a questionnaire given before and after the activity. The measurement results before the activity were obtained 6 children who had less interpersonal intelligence and after the activity there were 2 children who had less interpersonal intelligence. This activity found that playing traditional games can develop children's intelligence. Parents and school teachers are expected to be able to introduce and apply traditional games in the home and school because of their benefits both for the development of interpersonal intelligence and as an effort to preserve traditional Indonesian games.